2013
DOI: 10.1063/1.4811754
|View full text |Cite
|
Sign up to set email alerts
|

Bulk and interface trapping in the gate dielectric of GaN based metal-oxide-semiconductor high-electron-mobility transistors

Abstract: Articles you may be interested inQuantitative characterization of interface traps in Al2O3/AlGaN/GaN metal-oxide-semiconductor high-electronmobility transistors by dynamic capacitance dispersion technique Appl. Phys. Lett. 103, 033510 (2013); 10.1063/1.4813912 Study of gate oxide traps in HfO2/AlGaN/GaN metal-oxide-semiconductor high-electron-mobility transistors by use of ac transconductance method A comprehensive analytical model for threshold voltage calculation in GaN based metal-oxide-semiconductor high-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…Relative few studies reported on analysis of slow traps (>10 s) [12,13], which might affect the long term stability of these devices. Recently, V TH transient was used for the trap analysis on the AlGaN/GaN MIS-HEMTs with a gate dielectric of Al 2 O 3 [14]. However, the trapping/de-trapping phenomena still remain unclear under the gate dielectrics of in-situ Si 3 N 4 .…”
mentioning
confidence: 98%
“…Relative few studies reported on analysis of slow traps (>10 s) [12,13], which might affect the long term stability of these devices. Recently, V TH transient was used for the trap analysis on the AlGaN/GaN MIS-HEMTs with a gate dielectric of Al 2 O 3 [14]. However, the trapping/de-trapping phenomena still remain unclear under the gate dielectrics of in-situ Si 3 N 4 .…”
mentioning
confidence: 98%
“…It means that only a limited number of the interface states can be detected during the standard C-V measurements. Although several groups have proposed new methods to characterize electronic states in the MOS-HEMT structures, [14][15][16][17] there have been few reports on MOS interface state densities of the GaN-based MOS-HEMTs and their relationship to the resulting electrical properties has not been discussed in detail.…”
Section: Introductionmentioning
confidence: 99%
“…Two complementary techniques were used: (1) D it in the energy range of E C -E ¼ 0.5-1.0 eV was determined using V th -transients, deduced from the capacitance transients measured at V g %V th À0.5 V at temperatures of 25, 75, and 125 C. Only relative change (DV th ) between V th transients measured after "filling" pulse V F ¼ 0 (no filling) and V F ¼ 1.5 V (interface traps filling) was used for D it determination, to cancel out possible bulk trapping process (i.e., V th drift) previously discussed in Ref. 15. D it (E) was determined from the time derivative of DV th -t. (2) Filtered light-assisted V th transient technique was used to determine D it distribution of very deep interface states in the range of 1.75-3.25 eV below E C .…”
Section: Methodsmentioning
confidence: 99%
“…In contrast to Ref. 15, the light was exposed 50 s after beginning of the transient and kept exposed until the termination of the measurement. Finally, the C-V curves of the MOS-HEMT structures were calculated using a numerical solver of the one-dimensional Poisson equation with the Shockley-Read-Hall statistics accounting for the interface traps response, taking the measurement time into account.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation